Junior university: fostering young minds’ interest in higher education - Silva, Vítor; Urbano, Diana; Pinto, Isabel Macedo; Ribeiro da Silva, Maria D. M. C.; Graça, Pedro; Soares, Susana; Almeida, Teresa (Frontiers in Education, 2024)
The lack of exposure to higher education (HE) and unfamiliarity with academic life are significant factors in youngsters' decisions about their future after school. Choosing a field of study requires commitment and hard work, influenced by social factors and economic constraints. Universities in Europe and globally, including Universidade do Porto (U.Porto, Portugal), a founding member of EUCU.net, have opened up to society, particularly schools and pupils. U.Porto, a leader in Northern Portugal, establishes connections with schools, communities, municipalities, and companies. Since 2005, Junior University (U.Jr) at U.Porto has offered pupils from K5 to K11 their first enjoyable and educational experience with university life. Annually, over 7000 pupils engage with various academic fields at U.Porto, aiding informed vocational choices and fostering a desire for higher education. Since its inception, U.Jr has had a profound impact, consistently receiving positive feedback. Follow-up surveys show its significant role in encouraging enrolment in higher education, particularly at U.Porto. This study analyzes data from U.Jr participants and U.Porto first-year students from 2006 to 2022, revealing that one in four U.Porto enrollees during the national application process has previously attended U.Jr.